Change Management on Employee Performance in the Airlines Industry - Agustinus Numberi; Wilhelmina Anastasia I Arfusau (AIBPM Publisher, 2025)
This study examines the influence of change management practices on employee performance in the Indonesian airline industry by focusing on five key dimensions: organizational structure, leadership, organizational culture, communication, and technology. A quantitative explanatory research design was employed using primary data collected through structured questionnaires distributed to 120 employees of an airline company in Indonesia, with 100 valid responses analyzed. Statistical analysis using SPSS was conducted to test reliability, correlation, and regression relationships. The results indicate that organizational structure, leadership, organizational culture, and communication do not have a statistically significant effect on employee performance, while technology demonstrates a strong and positive influence, highlighting its important role in improving employee effectiveness in a highly dynamic and technology-driven aviation industry. Although this study is limited to a single airline company, the findings provide insights into the growing importance of technology-oriented change management in supporting organizational performance. Future research is recommended to involve multiple airlines and broader geographical coverage to improve generalizability and further explore employee adaptability in the evolving aviation sector.